Evaluating Contractor Performance through Cost-Time Management Strategies in Educational Building Project - Maw, Me Me; Murtika, I Wayan; Putra Atmaja, Sang Kompiang Rizki (Universitas Pendidikan Nasional, 2025)
Project performance is a critical indicator in assessing the effectiveness and efficiency of construction projects, particularly in terms of cost and time management. This study aims to analyze the key factors influencing contractor performance in the classroom rehabilitation project in Bali, focusing on cost and time aspects. Data were collected through questionnaires distributed to 30 respondents, including contractors and consultants directly involved in the project. The findings indicate that thorough cost planning, strict budget control, and effective cost risk management significantly contribute to project success. Likewise, realistic scheduling, regular progress monitoring, and inter-team coordination are essential in ensuring timely project delivery. The use of technology and active stakeholder engagement further enhance operational efficiency. These results contribute to strengthening project management strategies, particularly for small-scale educational rehabilitation projects in Indonesia.